Syllidae (Annelida) from the Alborán Sea (Western Mediterranean), with the description of a new species of Paraehlersia San Martín, 2003 - Prado, Ainhoa; Martín, Guillermo San (Zootaxa, 2024)
A list of 35 species of Syllidae (Annelida) is reported from sublittoral bottoms (from 42 to 169 m) in the Alborán Sea (Western Mediterranean), together with the description of a new species (Paraehelersia pamelae n. sp.), including original drawings and SEM photos. The new species is characterized by its small size, compound chaetae of posterior segments with short, bidentate falcigers, with both teeth similar, the proximal tooth only slightly longer than the distal one, long spiniger-like chaetae all along body, and dorsal simple chaetae distally bifid. Finally, we compare this new species with all previously known species of Paraehlersia and provide a dichotomous key.